Synthesis of BODIPY FL-tethered ridaifen-B, RID-B-BODIPY, and its localization in cancer cells - Murata, Takatsugu; Komukai, Kyoka; Semba, Yuta; Murata, Eri; Sato, Fumi; Takano, Tomohiro; Tsuchiya, Kaho; Matsuda, Chihiro; Sakai, Anju; Yoneoka, Amane; Takahashi, Shunsuke; Nagahara, Yukitoshi; et al. (Frontiers in Chemistry, 2024)
We synthesized ridaifen-B boron dipyrromethene (RID-B-BODIPY) using 2-methyl-6-nitro benzoic anhydride (MNBA)-mediated dehydration condensation reaction between amino alkyl-tethered RID and BODIPY FL. Comparative experiments between dicyclohexylcarbodiimide (DCC) and MNBA for their coupling reactions demonstrated that MNBA is an effective condensation reagent for amines and BODIPY FL. A cell staining study with RID-B-BODIPY showed intracellular localization of BODIPY FL fluorescence, attributed to the RID-B structure, indicating the successful development of a tool for analyzing intracellular molecular behavior efficiently.